Relative age Effect in collegiate soccer. influence of nationality, playing position, and class - Hurley, E.; Comstock, A. B.; Haile, L.; Beyer, S. K. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to evaluate the existence of relative age effects (RAEs) in collegiate soccer. In addition, the impact of nationality, position, class, and National Collegiate Athletic Association (NCAA) tournament qualification status on the prevalence of RAEs was assessed. Birth dates from male NCAA Division I soccer athletes (n = 4,082) from the 2017/2018 season were categorized into quarters based on calendar and scholastic quarters. All athlete birth-date distributions were compared with the expected birth-date distributions for the United States. International-born athletes (INT) displayed a significant difference in birth-date distribution when assessed with calendar quarters, whereas American-born athletes (USA) showed a significant difference in birth-date distributions when assessed with scholastic quarters. Furthermore, INT showed significant RAEs for midfielders and defenders, whereas USA showed significant RAEs midfielders and goalkeepers. In terms of class, INT had significant RAEs for all classes, whereas USA had significant RAEs only for freshmen and sophomores. All INT had significant RAEs regardless of tournament qualification status; however, USA had significant RAEs only for nontournament teams. In summary, significant RAEs exist in male Division I college soccer; however, the presence of RAEs is influenced by nationality, position, class, and NCAA tournament qualification status. Coaches should be aware of RAEs during the recruitment process to avoid potential selection bias.